Failure Mechanism and Dynamic Response Characteristics of Loess Slopes Under the Effects of Earthquake and Groundwater - Chai, Shaofeng; Wang, Lanmin; Wang, Ping; Pu, Xiaowu; Xu, Shiyang; Guo, Haitao; Wang, Huijuan (Frontiers in Earth Science, 2022)
A large-scale shaking table test was conducted with simulated earthquakes and groundwater to study the dynamic response and instability mechanism of a loess slope with a saturated bottom. By examining the acceleration, dynamic pore water pressure, corresponding soil pressure and observed macroscopic failure behaviour of the slope under different shaking intensities, the dynamic responses of acceleration and pore water pressure of the loess slope were analysed. By comparing the time history curve of acceleration with the time history curves of pore water pressure and surrounding soil pressure, we found that the instability failure of the slope was first due to the continuous vibration that caused the local structure of the slope soil to be damaged, forming locally saturated soil and the rise in the groundwater table during shaking. Then, the saturated soil liquefied under the action of strong vibration, and the liquefied soil mass slid under the action of a high-intensity earthquake force. Finally, the acceleration and spectral characteristics of the pore water pressure changed sharply with a shift in the predominant frequency at the liquefied locations under a high shaking intensity. The significant changes in dynamic pore water pressure mainly occurred when the shaking components in the low-frequency bands below 1 Hz. This implied that the shift in the frequency mainly resulted from the damage in the structure of the loess slope after high-intensity shaking. These results help us better understand the triggering mechanism and failure mechanism of saturated loess slopes during the Minxian-Zhangxian earthquake.